Internet-based cognitive rehabilitation for WORking Cancer survivors (i-WORC): study protocol of a randomized controlled trial - Klaver, Kete M. (Trials, 2020)
BACKGROUND: Cognitive problems are common in non-central nervous system cancer survivors. These problems are perceived as an important contributor to decline in work performance and work ability. Various interventions for cognitive problems have been proposed, but effectiveness regarding work-related outcomes has not yet been established. Effective treatment options to alleviate the adverse influence of cognitive problems on work performance are needed for working cancer survivors. In this paper, we will describe the design of a randomized, controlled, multicenter trial that evaluates the (cost-)effectiveness of an Internet-based cognitive rehabilitation program for occupationally active cancer survivors confronted with cognitive problems. METHODS/ DESIGN: A three-armed randomized controlled trial will be conducted, including two intervention groups (i.e., basic and extensive cognitive rehabilitation program) and one waitlist control group. In total, 261 cancer survivors (18–65 years) who have returned to work and who experience cognitive problems will be recruited. Patients with and without cognitive impairment as established in a neuropsychological assessment will be eligible; stratification will take place based on the presence of this cognitive impairment. The extensive intervention arm will contain a comprehensive training program (including psycho-education, fatigue management, and cognitive strategy training) with individual guidance (blended intervention). The basic intervention arm will contain a brief cognitive training program (including psycho-education and fatigue management) without individual guidance. The primary outcome will be accomplishment of an individually defined work-related treatment goal. Secondary outcomes include, among others, subjective cognitive functioning, work functioning, and quality of life. Primary and secondary outcomes will be measured at baseline (T0) and at 12 weeks (T1) and 26 weeks (T2) post-randomization. DISCUSSION: About 40–50% of the cancer patients worldwide are of working age at time of diagnosis. Many of the occupationally active cancer survivors experience cognitive problems. Both from an individual and a societal perspective, it is important to sustain cancer survivors’ employability. An effective treatment to alleviate the impact of cognitive decline and to improve work ability might help cancer survivors to sustain employability. TRIAL REGISTRATION: ClinicalTrials.gov NCT03900806. Registered on 03 April 2019 (current status: ongoing).